Reverse orders of reactivities in the polymerization of cyclic esters using N2O2aluminium alkoxide complexes - Khamphee Phomphrai (2018)
Three aluminium alkoxide complexes containing N2O2bis(phenoxy)-amine ligands were synthesized from reactions of the corresponding N2O2ligands with Al(OiPr)3in toluene. Different amine side chains of the ligands included pyridine (1), CH2NMe2(2), and CH2NEt2(3). The related chloro aluminium analog (4) was prepared from a reaction between AlCl3and the potassium salt of the N2O2ligand having CH2NMe2side chain. X-Ray crystallography reveals that complexes 3 and 4 have a monomeric five-coordinate aluminium center. Complexes 1-3 catalyzed the polymerization of ε-caprolactone (ε-CL) at 70 °C in toluene with the relative reactivities of 1 < 2 < 3. In contrary, only complex 1 was active for the polymerization of lactide under the same polymerization conditions.1H NMR spectroscopy shows that treatment of 2 with 1 equivalent of lactide afforded the ring-opened product L2Al-OCH(Me)C(O)OCH(Me)C(O)OiPr. Electronic effects are believed to be responsible for the observed trend in the ε-CL polymerization rates. On the other hand, steric hindrance at the amine side chain is the main contributor to the observed rates of lactide polymerization. © The Royal Society of Chemistry 2010.